2020
DOI: 10.1111/csp2.279
|View full text |Cite
|
Sign up to set email alerts
|

Illegal killing of nongame wildlife and recreational shooting in conservation areas

Abstract: Illegal killing of nongame wildlife is a global yet poorly documented problem. The prevalence and ecological consequences of illegal killing are often underestimated or completely unknown. We review the practice of legal recreational shooting and present data gathered from telemetry, surveys, and observations on its association with illegal killing of wildlife (birds and snakes) within conservation areas in Idaho, USA. In total, 33% of telemetered long-billed curlews (Numenius americanus) and 59% of other bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…A particularly troubling finding from our study is that the apparent leading cause of AY3 golden eagle mortality in the western United States is shooting, accounting for nearly 700 golden eagle deaths annually. This finding is consistent with other recent work documenting high rates of illegal shooting of raptors and other species in Idaho (Katzner, Carlisle, et al, 2020). Purposeful killing of golden eagles is a criminal infraction under the Eagle Act, yet prosecution and associated penalties apparently have been insufficient to curtail widespread shooting.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A particularly troubling finding from our study is that the apparent leading cause of AY3 golden eagle mortality in the western United States is shooting, accounting for nearly 700 golden eagle deaths annually. This finding is consistent with other recent work documenting high rates of illegal shooting of raptors and other species in Idaho (Katzner, Carlisle, et al, 2020). Purposeful killing of golden eagles is a criminal infraction under the Eagle Act, yet prosecution and associated penalties apparently have been insufficient to curtail widespread shooting.…”
Section: Discussionsupporting
confidence: 93%
“…Our IPM results suggest the proportion of AY3 golden eagles breeding each year in the coterminous western United States was high and temporally stable, but we did not allow for breeding by younger individuals in our IPM. Yet, golden eagles in subadult plumage (primarily Y3 in this context, Katzner, Kochert, et al, 2020) can and do successfully breed (Hunt et al, 2017; Murphy et al, 2019; Steenhof et al, 1983), likely most often in situations where there are insufficient numbers of AY3 individuals to fill all available breeding opportunities. As relevant examples, Whitfield et al (2004) demonstrated that the proportion of breeding golden eagles in subadult plumage in Scotland increased in areas where eagles were being persecuted and adult mortality was high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations